[East Indian woman, Trinidad] - (:unkn) unknown (My University, 2008)
An East Indian female vendor sitting in front of her produce with her hands heavily adorned with hand bands.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; Jewelry--India; Bracelets--India; Earrings--India; Street vendors--Trinidad and Tobago; Trinidad and Tobago